Identifying The Potential Sources of Chemical Elements in Drainage and Rivers Using Google Earth Imageries and Posteriori Knowledge - Awang, N. W.; Mahmud, M. R.; Ting, S. K.; Yi, T. J.; Noor Rashid, N. A. (International Journal of Integrated Engineering, 2022)
This study attempts to identify the potential sources of the chemical elements in the river and drainage water using in-situ water quality sampling and public domain satellite data. Monitoring the physico-chemical level of urban streams and rivers is important to secure sufficient water resources, an indicator to the ecological degradation in urban areas and an indicator of environmental pollution. Nonetheless, identifying the potential sources of chemical pollutants by field observation is constrained by hard labor activities, time, and cost. Having satellite imagery that provides land use activity information would be useful in determining the chemical sources. Therefore, the objective of this paper is to utilize the publicly accessible Google satellite images in identifying the potential sources of the chemical elements' presence in the water that is physically sampled and measured over the selected urban rivers and drainage of Johor Bahru. Three chemical elements were identified, ammonia (NH3), nitrate (NO3-), and phosphate (PO43-). The identification of the chemical sources is conducted based on the interpretation of the satellite-derived information together with the posteriori knowledge, experience, and inputs in an environmental chemistry perspective. The findings revealed that the proportion of land used did not always have a significant impact on the chemical content of the waterways. For ammonia, areas with significant hotspots (aquaculture, wet market) are more significant, although the size of the area is not dominant. The nitrate content, on the other hand, showed quite a distinct pattern linked to oil palm, intensive farming, and industrial or commercial areas. There was no distinct land use pattern associated with phosphate level. However, locations with high residential areas were likely to have high phosphate content in their respective waterways or drainage to the onsite investigations with minimal labor works, cost effective, and time efficient.